Aquachloridobis(2-{ 3-(morpholin-4-yl)propyl iminomethyl}phenolato)manganese(III) monohydrate - Hisham, N.A.I.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, [Mn(C14H19N2O2)(2)Cl(H2O)]center dot H2O, the Mn-III atom is N,O-chelated by two monoanionic Schiff bases, forming two six-membered chelate rings. One Cl atom and one water molecule in trans positions complete a distorted octahedral geometry around the metal atom. In the crystal, the complex molecules and the uncoordinated water molecules are connected via O-H center dot center dot center dot N, O-H center dot center dot center dot O and O-H center dot center dot center dot Cl hydrogen bonds into layers parallel to the ac plane and these are consolidated by C-H center dot center dot center dot pi interactions. The layers are further linked into a three-dimensional network through C-H center dot center dot center dot O interactions.